Artificial Intelligence and the Transformation of Sustainable Rural Consumers’ Buying Behaviour: A Study in Andhra Pradesh, India - Somasekhara, Margani (Nepalese Journal of Management Science and Research, 2026)
Artificial Intelligence (AI) can play a major role in transforming sustainable consumption in rural India, with Andhra Pradesh offering an important example. While the state has advanced digital initiatives at the policy level, many rural communities still struggle with limited digital literacy, low access to devices, and socio-economic barriers. This creates a paradox: strong readiness on paper, but real challenges on the ground. At the same time, AI in agriculture is already showing promise by helping farmers cut costs, reduce risks, and adopt sustainable practices naturally. However, a fully digital e-commerce model may not work in such settings; instead, a hybrid approach that combines AI with human networks is more effective. The study underscores that purely digital models, such as e-commerce platforms, are less effective in rural contexts. More viable outcomes emerge from hybrid approaches that integrate AI technologies with local human networks. Ethical concerns, particularly data privacy and algorithmic bias, are more pronounced in rural areas where social and economic inequalities already exist. To overcome these challenges, policymakers must prioritize closing the digital divide through improved infrastructure and targeted training initiatives. At the same time, businesses should design AI solutions that address genuine rural needs and deliver clear, tangible value to consumers. Sustainability must be embedded into these solutions from the outset rather than treated as an afterthought. Ultimately, meaningful success depends on deploying AI in a deliberate, strategic, and people-centric manner